PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA, DAN PENGALAMAN KERJA TERHADAP PENINGKATAN KINERJA KARYAWAN (STUDI KASUS PADA KARYAWAN PT. BPRS BHAKTI SUMEKAR SUMENEP) - Siti Nur Azizah Djamil; Muninghar Muninghar; Fatimah Riswati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2020)
This type of research is explanatory research research, the approach used is a quantitative approach with a total sample of 150 employees. The purpose of this study is 1). To find a description of the organizational culture, work environment, work experience and employee performance of PT. BPRS Bhakti Sumekar Sumenep. 2). To prove and analyze whether organizational culture, work environment and work experience simultaneously and significantly influence the performance of employees of PT. BPRS Bhakti Sumekar Sumenep. 3). To prove and analyze whether the organizational culture, work environment and work experience partially and significantly influence the performance of the employees of PT. BPRS Bhakti Sumekar Sumenep. 4). To analyze which variables among the organizational culture, work environment and work experience have a dominant influence on the performance of the employees of PT. BPRS Bhakti Sumekar Sumenep.The results showed that 1). Simultaneously, organizational culture, work environment and work experience responded very well by respondents so that it has a significant influence on employee performance at PT. BPRS Bhakti Sumekar Sumenep, proven the truth and accepted the hypothesis. 2). Partially, organizational culture, work environment and work experience responded very meaningfully / very well by employees so that it has a significant influence on the performance of employees of PT. BPRS Bhakti Sumekar Sumenep, proven the truth and accepted the hypothesis. 3). Work experience has a dominant influence on employee performance at PT. BPRS Bhakti Sumekar Sumenep, proven the truth and accepted the hypothesis.